Model Pendampingan Peningkatan Kinerja Pemasaran Kelompok Sadar Wisata Desa Kebonmanggu Kabupaten Sukabumi - Asep Muhamad Ramdan; Leonita Siwiyanti; Erik Candra Pertala; Novy Anggraini; Dicky Jhoansyah (ACADEMICS IN ACTION Journal of Community Empowerment, 2022)
Karangpara tourism place is surrounded by natural scenery with unique rock views and has beautiful photoshoot areas in some spots, for instance: hot air balloons, hanging bicycles, cloud windows, and others. This place is managed directly by a community that is part of a member of the Tourism Awareness Group (Pokdarwis). Karangpara tourism has great potential to grow. However, the number of tourists who had come to visit this place is lower than expected. Pokdarwis' problems in Karangpara tourism marketing can be explained as follows: the weakness of the marketing strategy in the promotion section, inefficiency in social media networks (conventional marketing), and marketing performance. The implementation method is carried out through two stages, namely the preparation stage and the implementation stage of the promotion design process. The implementation stage in the promotion design process is divided into several stages, including the implementation stage of the pamphlet making process, making profile videos, making event calendars, and making social media for Karangpara tourism. The results of the Matching Fund Model for Development of Integrated Tourism Objects Based on Social Empowering, a collaboration of community service activities between lecturers and students of the Muhammadiyah University of Sukabumi with the Kedaireka scheme is given training and assistance of Karangpara Tourism Awareness Groups in order to improve marketing performance. The solution offered in this service activity is to make and design effective and efficient promotional media such as profile videos, event calendars, and social media.